The Education of Religion Based Upon Students’ Active Participation - Batar, Yusuf (Yediveren Kitap, 2009)
In this study, It is dwelled upon the importance and the necessity of edu-cation of religion based upon the active participation of student. Bases of active education of religion and data of pedagogy are tried to be studied by the media-tion of basic approach of religion. Islam, actually, is based on the obedienceness and willingness, that’s why it is emphasized that education of religion cannot be practiced by repressive and compelling methods. Some principles that have to be applied during education process by the perspective of education of religion based on active and willing participation of students are analyzed thoroughly. It is handled the matters make the student ac-tive figure of education process in the context of cited principles. Besides, it is ex-amined education of religion based upon active participation determining effect on students’ formation of concept of religion and their personalities.

Bu çalismada ögrencinin aktif katilimina dayali din egitiminin önemi ve ge-rekliligi üzerinde durulmustur. Dinin temel yaklasimindan ve pedagojinin verilerin-den hareketle etkin din egitiminin esaslari incelenmeye çalisilmistir. Islam dininin gönüllülük esasina dayali itaat etme ve boyun egme yaklasimi isiginda, din egitiminin de baskici ve dayatmaci bir tarzda olamayacagi sebepleriyle birlikte ele alinmistir. Ögrencinin gönüllü ve aktif katilimina dayali bir din egitimi perspektifiyle, egitim sürecinde uyulmasi gereken bazi prensipler etraflica tahlil edilmistir. Söz ko-nusu prensipler çerçevesinde, ögrenciyi egitim sürecinin aktif bir unsuru haline getirecek olan hususlar üzerinde durulmustur. Ayrica aktif katilima dayali din egitiminin, ögrencide din anlayisinin olusumu ve kisilik olusumu üzerindeki belirley-ici etkisi üzerinde durulmustur.
Ögrencinin Aktif Katilimina Dayali Din Egitimi
Keywords: Religion; Society and Culture Studies; Din; Toplum ve Kültür Arastirmalari